Genetically Modified Crops’ Technology and its Awareness among Smallholder Farmers in Nigeria - Ogheneruemu Obi-Egbedi; Omowunmi Ogungbite; Isaac Oluwatayo (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Genetically Modified (GM) crops are crops modified through genetic engineering to improve their quality. Although safety concerns about genetically modified organisms (GMOs) are still being debated, the food security benefits have led to adoption by many counties. In Nigeria, where most farmers are uneducated and likely unaware of the agricultural technology, the government approved its first biotechnology crop for commercialization in 2018. Level of farmers’ awareness is crucial to acceptance of GM crops, although; this has not been fully explored in the literature. Therefore, this study aimed to assess farmers’ awareness for GM crops and the factors that determine their awareness in Oyo state, Nigeria, using primary data collected in 2018 with the aid of well-structured questionnaires from 242 smallholder farmers. Principal component analysis and Tobit regression model were used for data analysis. Results showed that farmers were aged 43 years with farm size of 3.57 ha, farming experience of 14 years and 11 years of education. Most farmers were male (71.90%), married (67.36%), not members of farmer groups (64.46%) and sourced their seeds from non-credible sources (85.12%). Most farmers (52.07%) had either not heard of or did not know of any benefits/costs of GM crops, hence; were not aware of GM crops. Factors that influenced awareness of GM crops were being a male farmer, years of education and source of seeds. The study concluded that increasing years of education and ensuring use of credible seed sources will increase awareness of the costs and benefits of GM crops among farmers.